Analisis Local Culture Batak Toba dalam Film Ngeri-Ngeri Sedap Sutradara Bene Dion Melalui Mise En Scene - Muhammad Rafli Sajali; Dani Manesah (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2024)
Ngeri-ngeri Sedap is a comedy-drama film set in a Batak family, directed and scripted by Bene Dion Rajagukguk, based on an adaptation of the novel of the same name by Bene Dion. Ngeri-ngeri Sedap received positive reviews and was commercially profitable. The movie also represented Indonesia in the 95th Academy Awards or Oscars. This research aims to describe the value of local Toba Batak culture through mise-en-scene. This type of research is qualitative research with descriptive method. The data source of this research is the movie Ngeri-Ngeri Sedap which lasts 1 hour 53 minutes. The results of this study indicate the analysis of Toba Batak local culture through the mise-en-scene aspect. The local culture of Batak Toba contained in the film "Ngeri-ngeri Sedap" can be seen from the setting, costumes and make-up used by the players, the movement of the players (acting) and the dialog spoken by the players.